Analysis of the COVID-19 vaccine willingness and hesitancy among parents of healthy children aged 6 months–4 years: a cross-sectional survey in Italy - Postiglione, Mario; Miraglia del Giudice, Grazia; Della Polla, Giorgia; Angelillo, Italo Francesco (Frontiers in Public Health, 2023)
In Italy, since December 2022, COVID-19 vaccination was extended to children aged 6 months-4 years with conditions of fragility and for those healthy at request of the parent. The purposes of the cross-sectional survey were to determine the willingness and hesitancy of the parents/guardians to have their healthy children vaccinated against COVID-19. The survey was performed among 389 parents/guardians with a child aged 6 months-4 years randomly selected fromseven kindergartens and eight nursery schoolsin the geographic area of Naples, Italy.Only 10.5% were very concerned about the risk of infection and the mean values regarding the perceived utility and safety of COVID-19 vaccine were 3.3 and 3.2, respectively. Only 13.7% participants were willing to consent to vaccinate the selected child against COVID-19, while 20.1% were uncertain, and 66.2% did not intend. Parents/guardians of older age, those who received information about COVID-19 vaccine from physicians or pediatricians, those who believed that COVID-19 vaccine is useful, and those with lower hesitancy regarding the COVID-19 vaccine were more willing to vaccinate their child. The mean Parent Attitudes About Childhood Vaccines (PACV-5) score was 5.6, with 33.1% of respondents who were identified as high-hesitant towards COVID-19 vaccination(score >7). Parents/guardians with a lower perceived safety of the COVID-19 vaccine were more likely to be highly hesitant. The findings reveal the need to improve community-based education campaigns and effective promotion on COVID-19 vaccination for increasing the willingness and addressing parental safety concerns.